Keputusan Pembelian Lipstik Pada Mahasiswi STIE Cendekia - Fitri Widhiastutik; Ari Kuntardina (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2022)
The development of the cosmetic industry, especially lipstick is growing tremendously. The lipstick market segment expanded towards the teen segment. Many lipstick products are offered by manufacturers to adolescent consumers. With so many choices make teenagers more selective in choosing products. The quality of lipstick is one of the factors they consider, considering the health risks of the skin when exposed to poor quality lipstick. Teenagers also do not have their own income, so in making lipstick purchases the price factor is also considered. The research purposes are to find out the influence of product quality and price on the decision to buy lipstick at STIE Cendekia Bojonegoro students. Quantitative research with a population of 165 STIE Cendekia students class A with a sample of 62 respondents. Sampling technique using proportionate stratified random sampling. Data collection through questionnaires. Data analysis uses multiple linear regression analysis. The results showed that partially the quality of the product and the price had a significant effect on the decision to buy lipstick. This is an opportunity for the next researcher to examine other factors that contribute to the decision to buy lipstick